Shale gas and hydraulic fracturing in South Africa: towards a petroleum legal framework that provides for innovative technologies that support energy security of supply and mitigate climate change - Sayidini, Bongani (Department of Private Law, 2023)
It is estimated that South Africa contains vast amounts of shale gas. Meanwhile, the country relies heavily on coal as a primary energy source, as a result, it ranks amongst the highest carbon dioxide emitting countries globally, therefore is a significant contributor to climate change. Climate change is a cause for global concern, if not mitigated it will cause more severe devastation to societies worldwide. The exploitation of shale gas in South Africa will require the use of hydraulic fracturing, a technology that has generated controversy globally. The country however does not have an effective legal framework to regulate the exploration and production of shale gas using this technology. This thesis investigates whether South Africa's petroleum legal framework provides adequately for the protection of the environment against the risks posed by shale gas development. It posits that with a petroleum legal framework premised on avoiding, mitigating, and remediating environmental damage, shale gas could be developed in an environmentally sensible manner in South Africa, to enhance energy security of supply while reducing the country's carbon dioxide emissions to the atmosphere. The assessment employs the comparative legal research methodology and uses the prevention principle (avoidance), precautionary principle (mitigation), and polluter pays principle (remediation) as comparative themes. The comparative jurisdictions are South Africa, the United Kingdom, and Canada. The United Kingdom and Canada are more mature petroleum provinces/jurisdictions, therefore, have relatively advanced legal frameworks for petroleum extraction. The study finds that these principles are already embedded in the South African environmental legal framework. Therefore, the appropriate petroleum legal framework to guide shale gas development in South Africa would be one that provides for the rigorous application of these principles, in an integrated and complementary manner, with close monitoring and enforcement. The capacity of the relevant regulatory agencies will have to be enhanced to ensure effective compliance monitoring and enforcement.